Osteoporosis and dermatoporosis: a review on the role of vitamin D - Romano, Fiammetta; Serpico, Domenico; Cantelli, Mariateresa; Di Sarno, Antonella; Dalia, Carmine; Arianna, Rossana; Lavorgna, Mariarosaria; Colao, Annamaria; Di Somma, Carolina (Frontiers in Endocrinology, 2023)
and Dermatoporosis (DP) are expressions of the aging process at the skin and bone levels, respectively. Both conditions are associated with increased morbidity for elderly people, and this requires necessary interventions. They share many common risk factors; among these, vitamin D (VD) deficiency appears to have a role. VD is involved in either disease with many mechanisms, among which immunomodulation. VD deficiency has been linked to OP because it inhibits the body's capacity to absorb calcium and maintain optimal bone health. Available evidence suggests that proper vitaminosis D also appears to be vital in preventing skin age-related issues. DP is often seen in elderly individuals, particularly those with long-term sun exposure and a history of chronic sun damage. VD deficiency can be linked to DP, since its involvement in collagen production, epidermal barrier function, inflammation regulation, wound healing, and sun protection. Aim of this review is to summarize the most updated existing evidence on the role of VD in the development of fragility syndromes such as DP and OP and the possible benefits of VD supplementation as a simple and harmful weapon against aging.